Tryptophan Metabolism in Inflammaging: From Biomarker to Therapeutic Target - Sorgdrager, Freek J. H.; Naudé, Petrus J. W.; Kema, Ido P.; Nollen, Ellen A.; Deyn, Peter P. De (Frontiers in Immunology, 2019)
Inflammation aims to restore tissue homeostasis after injury or infection. Age-related decline of tissue homeostasis causes a physiological low-grade chronic inflammatory phenotype known as inflammaging that is involved in many age-related diseases. Activation of tryptophan (Trp) metabolism along the kynurenine (Kyn) pathway prevents hyperinflammation and induces long-term immune tolerance. Systemic Trp and Kyn levels change upon aging and in age-related diseases. Moreover, modulation of Trp metabolism can either aggravate or prevent inflammaging-related diseases. In this review, we discuss how age-related Kyn/Trp activation is necessary to control inflammaging and alters the functioning of other metabolic faiths of Trp including Kyn metabolites, microbiota-derived indoles and nicotinamide adenine dinucleotide (NAD+). We explore the potential of the Kyn/Trp ratio as a biomarker of inflammaging and discuss how intervening in Trp metabolism might extend health- and lifespan.